Unraveling the Spatiotemporal Human Pluripotency in Embryonic Development - Ávila-González, Daniela; Portillo, Wendy; García-López, Guadalupe; Molina-Hernández, Anayansi; Díaz-Martínez, Néstor E.; Díaz, Néstor F. (Frontiers in Cell and Developmental Biology, 2021)
There have been significant advances in understanding human embryogenesis using human pluripotent stem cells (hPSCs) in conventional monolayer cultures and their self-organization in 3D. Thus, in vitro models have contributed to elucidating the molecular mechanisms for specification and differentiation during development. However, the molecular and functional spectrum of human pluripotency (i.e., intermediate states, pluripotency subtypes and regionalization) is still not fully understood. This review describes the mechanisms that establish and maintain pluripotency in human embryos and their differences with mouse embryos. Further, it describes a new pluripotent state representing a transition between naive and primed pluripotency. This review also presents the data that divide pluripotency into substates expressing epiblast regionalization and amnion specification as well as primordial germ cells in primates. Finally, this work analyzes the amnion's relevance as an organizer for regionalization before the onset of gastrulation.